2018
DOI: 10.1007/s00262-018-2164-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of MDA5 and interferon-I in dendritic cells for T cell expansion by anti-tumor peptide vaccines in mice

Abstract: Cytotoxic T lymphocytes (CTLs) are effective components of the immune system capable of destroying tumor cells. Generation of CTLs using peptide vaccines is a practical approach to treat cancer. We have previously described a peptide vaccination strategy that generates vast numbers of endogenous tumor-reactive CTLs after two sequential immunizations (prime-boost) using poly-ICLC adjuvant, which stimulates endosomal toll-like receptor 3 (TLR3) and cytoplasmic melanoma differentiation antigen 5 (MDA5). Dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
0
26
0
2
Order By: Relevance
“…We previously reported that intravenous injections of PICLC into mice resulted in more than 10-fold higher production levels of IFN-I as compared with poly-IC, which was mediated by MDA5 and not TLR3. 32 Several experiments presented here provide evidence that the stromal cells responding to PICLC are VECs, which would make sense since these cells play a critical role in allowing T cell infiltration into tissues where they are needed. It is well-known that VECs express numerous scavenger receptors allowing them to capture molecules such as lipids and nucleic acids.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We previously reported that intravenous injections of PICLC into mice resulted in more than 10-fold higher production levels of IFN-I as compared with poly-IC, which was mediated by MDA5 and not TLR3. 32 Several experiments presented here provide evidence that the stromal cells responding to PICLC are VECs, which would make sense since these cells play a critical role in allowing T cell infiltration into tissues where they are needed. It is well-known that VECs express numerous scavenger receptors allowing them to capture molecules such as lipids and nucleic acids.…”
Section: Discussionmentioning
confidence: 75%
“…In vitro studies with DCs using a proton sponge inhibitor bafilomycin A1 have shown that IFN-I production by PICLC requires endosomal escape via this mechanism. 32 VECs stimulated with PICLC upregulated VCAM-I, CXCL10 and CXCL9, which play an important role in T cell tissue infiltration. 11 12 14 24 Interestingly, systemic administration of PICLC promoted T cell infiltration into tumors while not affecting much T cell infiltration into other organs.…”
Section: Discussionmentioning
confidence: 94%
“…TnTR1 TCR-transnuclear mice (Trp1 455-463 specific CTLs RAG1-KO) were described [23]. Transgenic mice that express the TCR specific for gp100 [25][26][27][28][29][30][31][32][33] (pmel-1 mice) [24], or Ova 257-264 restricted TCR (OT-1 mice), were purchased from The Jackson Laboratory. Trp1-KO B6 mice were generated in our facility by breeding F1 mice of TRP-1 TCR Bw RAG-mice (Jackson Laboratory Stock No.…”
Section: Mice and Cell Linesmentioning
confidence: 99%
“…In previous studies we reported that peptide vaccines administered with poly-ICLC adjuvant (TLR3 and MDA5 agonist) in a prime-boost protocol induced vast CD8 T cell responses that lead to significant antitumor effects in mice [17,[25][26][27]. Amphiphilic peptides such as those conjugates with palmitic acid chains (pam-peptides), which self-assemble into nanoparticles were more immunogenic than minimal peptide epitopes or long peptides (LPs) [17].…”
Section: The Impact Of Route Of Administration Of the Vaccine On T Cementioning
confidence: 99%
“…During the T cell activation, DC engages the T-cell receptor (TCR), secrete specific cytokines and stimulate the immune responses toward TH1, TH2, or Tregs depending on the cytokine environment. Due to their proficiency at antigen crosspresentation (i.e., the presentation to both CD4+and CD8+T cells), DC have been used as vaccine platforms to induce anti-tumor cytotoxic T lymphocyte (CTL) CD8 immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%